Unlocking The Charms of The Turkish Language: Exploring @speakinturkish on Instagram - Raesita Rakhmawati Rosadi; Muhamad Danu Winata; Rachmawati Windyaningrum (Jurnal Komunikasi dan Bisnis, 2023)
In conjunction with the rapid evolution of technology, education and learning are also undergoing development into diverse forms and channels. Social media, especially Instagram, is utilized by individuals of all ages, both young and old, as an integral aspect of daily life. Beyond its entertainment function, social media serves as a tool for education. On Instagram, numerous accounts dedicated to teaching the Turkish language can be found, among which @speakinturkish stands out as one of the most followed and interactive. This study aims to thoroughly examine the account's active role in Turkish language education, examine its posts and reels, assess their impact on followers, and uncover their contributions to literacy education. To achieve this, a combination of document analysis and discourse analysis methodologies was employed. The investigation encompassed an evaluation of various aspects, including page layout, content composition, posting frequency, approaches to Turkish language instruction, and pedagogical methodologies employed. Additionally, the study delved into the account's interaction with its followers, considering metrics such as likes, comments, and response frequency. This discourse encompassed discussions on the influence exerted by the commented accounts on their followers. Given the escalating prominence of technological integration, the research anticipates valuable insights that will enrich the language education and literacy.